2023
DOI: 10.1186/s12882-023-03092-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low-dose rituximab in minimal change disease and prevention of relapse

Abstract: Background Minimal change disease (MCD) is a major cause of nephrotic syndrome (NS) in children and a minority of adults. The higher tendency to relapse put patients at risk for prolonged exposure to steroids and other immunosuppressive agents. B cell depletion with rituximab (RTX) may be beneficial to the treatment and prevention of frequently relapsing MCD. Therefore, this study aimed to verify the therapeutic/preventive effects of low-dose RTX on the relapse in adult with MCD. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…There are 9 prospective studies [ 27 , 39 , 42 , 44 46 , 48 49 , 52 ] and 19 retrospective studies [ 26 , 28 38 , 40 41 , 43 , 47 , 50 51 , 53 ]. Five studies were conducted in USA [ 28 , 33 , 36 37 , 51 ], six studies in India [ 26 , 31 , 35 , 45 , 49 , 52 ], five in China [ 30 , 41 , 44 , 47 , 48 ], four studies in Japan [ 34 , 39 , 42 , 46 ], two each in France [ 40 , 43 ] and Spain [ 29 , 50 ] as well as one each in Netherlands [ 38 ], Sweden [ 27 ], Tunisia [ 32 ] and Pakistan [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are 9 prospective studies [ 27 , 39 , 42 , 44 46 , 48 49 , 52 ] and 19 retrospective studies [ 26 , 28 38 , 40 41 , 43 , 47 , 50 51 , 53 ]. Five studies were conducted in USA [ 28 , 33 , 36 37 , 51 ], six studies in India [ 26 , 31 , 35 , 45 , 49 , 52 ], five in China [ 30 , 41 , 44 , 47 , 48 ], four studies in Japan [ 34 , 39 , 42 , 46 ], two each in France [ 40 , 43 ] and Spain [ 29 , 50 ] as well as one each in Netherlands [ 38 ], Sweden [ 27 ], Tunisia [ 32 ] and Pakistan [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…21 studies [ 28 35 , 37 , 39 40 , 42 48 , 50 51 , 53 ] reported the baseline creatinine level of patients. 9 studies [ 28 , 29 , 31 , 32 , 35 , 40 , 43 , 51 , 53 ] reported a mean baseline creatinine of 1.08 mg/dL, 2 [ 33 , 34 ] studies reported a median baseline creatinine level of 0.69mg/dL and 0.9 mg/dL respectively whereas the other 10 studies [ 30 , 37 , 39 , 42 , 44 48 , 50 ] did not mention whether baseline creatinine level was calculated in mean or median. Extracted data from 11 studies [ 26 28 , 35 , 41 , 46 48 , 50 52 ] reported a mean rate of relapse of 33.33%, while the duration of remission from 6 studies [ 27 , 37 , 41 , 44 , 48 , 51 ] ranges between 1 to 43 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it is noteworthy that several respondents chose a substandard dosage. This reality may reflect findings from both Japanese and foreign studies that reported the effectiveness of a single 200-mg dose of RTX [22,23].…”
Section: Plos Onementioning
confidence: 99%
“…The recent discovery of anti-nephrin antibodies as a driver of autoimmunity in a subset of MCD underlines the importance of B cells in the pathogenesis of MCD [ 3 ]. There is evidence that rituximab is effective in the management of adult MCD [ 35 ]. A retrospective comparison of different second line therapies used in a single center to manage FR/SD MCD indicated that the median time to relapse after rituximab was longer (66 versus 28 months) compared with other measures (CNIs, mycophenolate mofetil, and cyclophosphamide) but the difference fell short of statistical significance [ 36 ].…”
Section: Introductionmentioning
confidence: 99%